IDENTIFICATION AND PHYSIOLOGICAL CHARACTERIZATION OF A CONSORTIUM OF HYDROCARBON-OXIDIZING BACTERIA OF OIL AND OIL PRODUCTS - T. N. Shapiro; G. A. Dolnikova; N. V. Nemtseva; D. A. Sandzhieva; E. S. Lobakova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2018)
A consortium of microorganisms were isolated from TC-1 fuel form, each member of which is capable of consistently degrade hydrocarbons’ different fractions. The 5 strains of hydrocarbon-oxidizing bacteria (PSB) were identified and isolated from TS-1 jet fuel. Their physiological and biochemical features are defined. All strains exhibit positive catalase activity. It is determined that all UOB strains, producing exogenous and endogenous surfactants, are capable to growth on media with different fraction of hydrocarbons. The study of these associations allows to create effective preparations for bioremediation in the elimination of accidental spills of oil and petroleum products.